PENGARUH FUNGSI AUDIT INTERNAL DAN LOVE OF MONEY TERHADAP KECURANGAN PELAPORAN KEUANGAN - Naa'imah, Siti; Nafiati, Lu'lu'; Rusdianto, Rusdianto (E-Jurnal Ekonomi dan Bisnis Universitas Udayana; VOLUME.14.NO.07.TAHUN.2025DO - 10.24843/EEB.2025.v14.i07.p10, 2025)
Fraudulent financial reporting is challenge in the business world that can harm stakeholders and undermine market integrity. This study aims to analyze the influence of internal audit functions and love of money on the tendency to commit financial reporting fraud. The research employs an experimental method with a 3x2 factorial design, where participants are categorized based on the strength of the internal audit function (strong, weak, and absent) and levels of love of money (high and low). The results indicate that a strong internal audit function significantly reduces individuals’ tendency to engage in fraudulent financial reporting, supporting the hypothesis that effective internal oversight mitigates fraud risk. However, love of money was not directly proven to influence fraudulent tendencies, although it can, under certain conditions, increase individuals’ motivation to act unethically. Additionally, the study finds that the interaction between a strong internal audit function and love of money helps mitigate its negative impact on fraudulent behavior. These findings have practical implications for companies and regulators in enhancing the effectiveness of internal audits and designing policies to reduce individual motivations for financial fraud.